Kurikulum Praktik Profesi Lapangan (PPL) Jurusan Tarbiyah STAIN KUDUS - Kisbiyanto, Kisbiyanto (THUFULA, 2014)
PPL is important for improving student skills. Therefore, curriculum of PPL must be sistematically organized. This research explained about (1) design and content of curriculum of PPL, (2) implementation and evaluation of PPL in State Islamic College of Kudus. This research were designed in the qualitative approach. Data were gathered by using observation and document. The validity and reliability were verified by credibility, transferability, dependability, and confirmability tests. The data were analyzed by using descriptive model. The result of research (1) the design and content of PPL for students in madrasah/islamic school with special approach in pragmatic or competence, and consist of both of teaching and school administration, (2) implementation and evaluation of PPL with higher standard for passing (70 /3,49).